2021
DOI: 10.1111/gcb.15866
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton and cyanobacteria abundances in mid‐21st century lakes depend strongly on future land use and climate projections

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 79 publications
2
17
0
1
Order By: Relevance
“…Kraemer et al 2017), under warmer climate and eutrophic conditions, a higher biomass of phytoplankton and dominance by potentially toxic cyanobacteria is expected. This a consistent result emerging from numerous recent studies (Paerl and Huisman 2008;Kosten et al 2012;Paerl and Paul 2012;Jeppesen et al 2014;Huisman et al 2018;Burford et al 2020) and research approaches such as modelling for individual temperate lakes and basins (Trolle et al 2011;Kakouei et al 2021); heating experiments (Hansson et al 2013, but see Feuchtmayr et al 2009and Kratina et al 2012; and latitudinal gradient and cross-comparative studies (Kosten et al 2012;Meerhoff et al 2012).…”
Section: Eutrophication and Climate Warming Synergy And Feedbacks Thr...supporting
confidence: 52%
See 1 more Smart Citation
“…Kraemer et al 2017), under warmer climate and eutrophic conditions, a higher biomass of phytoplankton and dominance by potentially toxic cyanobacteria is expected. This a consistent result emerging from numerous recent studies (Paerl and Huisman 2008;Kosten et al 2012;Paerl and Paul 2012;Jeppesen et al 2014;Huisman et al 2018;Burford et al 2020) and research approaches such as modelling for individual temperate lakes and basins (Trolle et al 2011;Kakouei et al 2021); heating experiments (Hansson et al 2013, but see Feuchtmayr et al 2009and Kratina et al 2012; and latitudinal gradient and cross-comparative studies (Kosten et al 2012;Meerhoff et al 2012).…”
Section: Eutrophication and Climate Warming Synergy And Feedbacks Thr...supporting
confidence: 52%
“…The best approaches for mitigating the effects of human activity on lake phytoplankton and cyanobacteria depend strongly on lake sensitivity to long-term change and the magnitude of projected climate changes and land use at a given location (Kakouei et al 2021). Although climate warming may promote eutrophication and its symptoms, eutrophication is still largely human-controlled.…”
Section: Advances In Mitigation and Adaptation Policiesmentioning
confidence: 99%
“…Rising wind speeds may increase the disturbance and reduce the surface area of PBs (Wu et al, 2015), while moderate precipitation may promote PB severity due to nutrient runoff (Ho & Michalak, 2020). Other catchment stressors (e.g., land use change) may interact with eutrophication and climate change, particularly in urban lakes in rapidly expanding cities (Kakouei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization generally leads to increased nutrient loading to the surrounding lakes (Kakouei et al, 2021), increased lake water temperature downwind and/or downstream of the city by heating the near surface temperature and inflowing rivers (LeBlanc et al, 1997; Tang et al, 2022). Meanwhile, urban expansions can increase suburban wind speeds by strengthening lake‐land breeze circulations (Liu et al, 2020; Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The global climate is changing [1,2], and this may affect the ecosystem structure and nutrient dynamics of lakes as well as their water quality. Several studies suggest that the biomass of phytoplankton and the concentration of chlorophyll a will increase, and also the relative contribution of cyanobacteria among the phytoplankton assemblage is expected to rise [3][4][5][6][7]. In correspondence with this, latitudinal gradient and cross-comparative studies have shown a greater importance of cyanobacteria in warm shallow lakes compared to colder temperate shallow lakes [6,8].…”
Section: Introductionmentioning
confidence: 99%